PERSONNEL SELECTION - BASIS OF TECHNOLOGY OF IT’S QUALITY MANAGEMENT (Regional aspects of productive forces development of Ukraine, 2019)
The article is devoted to the problems of personnel selection. It states that professional selection is the most important part of the hiring of employers; it mainly determines the effectiveness of personnel management. Therefore, the modern organizations give appropriate attention to the personnel selection.The article stresses that the priority tasks of increasing the efficiency of functioning of executive and management structures are: to equip them with employees who have the necessary qualities to successfully work in chosen profession, and the creation of a system that allows them to maintain and develop their working capacity, as well as reliability. To accomplish such tasks, periodic control of the employee’s functional status and the identification of objective criteria that characterize the qualitative composition of such units and bodies are necessary. And there is also a need for staff selection.The article examines the system of personnel selection. An analysis of the effectiveness of the existing selection system is carried out.The important tasks of professional psychological selection are the assessment of the development of the individual-psychological qualities and properties of the applicant’s personality, that are necessary for successful training and activities in the chosen specialty, as well as the conclusion on eligibility for training or practical activities in the relevant specialty.Measures to improve the personnel selection system are developed.The foreign experience of selection of personnel is estimated. However, copying of foreign methods of work with personnel without taking into account the characteristics of Ukrainian enterprises can have a significant negative effect - both economic and psychological. Since the mentality, traditions, peculiarities of the spiritual and socio-economic environment in which the person has grown and formed are of great importance in the work with people.The article states that professional and highly skilled personnel selection will have the subsequently positive affect on the reduction of staff turnover, greater employee satisfaction with the service and, as a result, greater efficiency of the organization.